A Study of Direct Listings and Reverse Mergers in Sweden - Javebrink, Gabriel; Zinga, Arzenije (My University, 2022)
In the last few years, alternative methods of taking a company to the public market have increased in popularity, such as direct listings and reverse mergers. Even though some information can be found about these alternative methods in existing theory, it can be concluded that this information is focused on the stock market in the USA, and not always applicable on the Swedish one. It is therefore of interest in this report to analyze these listing methods on the Swedish stock market, which brings us onto the aim of this report: To analyze the listing processes: direct listing and reverse merger, on the Swedish marketplaces.To help achieve this aim, the traditional way of going public, through an IPO, is compared with these two alternative methods. The IPO process in Sweden is described in the beginning of the theoretical framework, followed by a description of both direct listings as well as reverse mergers. Moreover, to give the reader a full understanding of the listing processes, the Swedish marketplaces are mapped and compared, as well as the possibilities that exist on the marketplaces regarding these alternative listing methods.Case studies have been included in this report to be able to compare with existing theories and therefore allow a higher confidence in the presented findings. Two companies that have done a direct listing in Sweden have been included as well as two companies that have done a reverse merger in Sweden. Moreover, interviews have been conducted with experts in the research area to gain information about the alternative listing methods that can be applied to the Swedish market with high accuracy.A direct listing in Sweden may be defined as a listing where no new capital can be raised, therefore only companies that are not in dire need of capital should opt for this method. On the other hand, a company that wants to experience a speedier listing process may opt for a reverse merger instead, even though this often means that they can not initially choose the marketplace they get listed on. The main implications of this report is for companies and entrepreneurs to gain a better understanding of these relatively unexplored listing methods - for them to be able to choose a listing method and a marketplace which are optimal for their specific case.Future research might include a case study with more companies that have done a direct listing or reverse merger on a Swedish marketplace, to see if the findings in this report are generalizable.
Keywords: Direct listing; Reverse merger; Initial public offering; Swedish stock market